The Taylor‐Couette Disc Contactor. Issue 11 (6th October 2016) - Grafschafter, Annika; Aksamija, Enes; Siebenhofer, Matthäus
Abstract: The Taylor‐Couette disc contactor is a hydrodynamic hybrid of a rotating disc contactor and a Taylor‐Couette contactor. For application in reactive bioseparations, this type of liquid‐liquid contactor may offer advantageous operation features. This paper summarizes the design characteristics of the Taylor‐Couette disc contactor. For hydrodynamic characterization, experimental data of the mean Sauter diameter and dispersed‐phase hold‐up were compared with results predicted by empirical correlations, which were originally developed for rotating disc contactors. Several correlations were modified for the application on Taylor‐Couette disc contactors. Operation characteristics have been deduced from mass‐transfer experiments on the pilot‐plant scale. Abstract : Liquid‐liquid extraction is a leading technology that can increase the economic feasibility of separation processes and provides access to both a chemical reaction and separation in one reactor. For application in reactive bioseparations, the Taylor‐Couette disc contactor may offer advantageous operation features. This paper investigates the hydro‐dynamic characteristics of the Taylor‐Couette disc contactor.